2022
DOI: 10.1038/s41598-022-22838-1
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes of the APOLLON observational study of intravitreal aflibercept monotherapy in France in patients with diabetic macular edema

Abstract: APOLLON (NCT02924311) was a prospective observational study to evaluate the effectiveness of intravitreal aflibercept (IVT-AFL) treatment of diabetic macular edema (DME) over 24 months in routine clinical practice in France. The primary endpoint was mean change from baseline in best-corrected visual acuity (BCVA; Early Treatment Diabetic Retinopathy Study letters) by 12 months, and safety was monitored throughout the study. Of 402 patients enrolled across 61 participating clinics and hospitals in France, 168 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…The safety profile of IVT-AFL was consistent with previous studies [ 13 , 25 27 ]. There was one case each of uveitis and endophthalmitis that were considered both serious and treatment-related.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The safety profile of IVT-AFL was consistent with previous studies [ 13 , 25 27 ]. There was one case each of uveitis and endophthalmitis that were considered both serious and treatment-related.…”
Section: Discussionsupporting
confidence: 89%
“…The functional and anatomic improvements achieved in patients with DME in AURIGA were similar to or greater than the gains observed in other prospective real-world studies of IVT-AFL. In the APOLLON study conducted in France, treatment-naïve and previously treated patients gained +6.5 letters overall between baseline and month 12 following 7.6 IVT-AFL injections ( n = 147) [ 24 ]; this decreased to +3.9 letters by month 24 after a mean total of 11.6 injections ( n = 168) [ 25 ]. From baseline to month 12, the reduction in CRT in APOLLON ranged from 130 to 138 µm across the two treatment cohorts.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 , 47 , 48 Numerous prospective and retrospective RWE studies involving these patients have provided complementary information about the effectiveness of intravitreal anti-VEGF agents on DME, particularly emphasizing the importance of number of follow-ups and injections to avoid undertreatment. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 …”
Section: Discussionmentioning
confidence: 99%
“… 20 , 50 Recently, the 2-year prospective APOLLON study from France reported a higher mean cumulative number of IVA injections (7.6 and 11.6) in 12 and 24 months, leading to +6.5 and +3.9 mean letter gains, respectively. 51 , 52 The authors attributed the relatively smaller visual improvements despite a higher number of IVIs at 2 years in the APOLLON study to structural changes related to the long-standing DME in previously treated patients. 52 One-year results of the global LUMINOUS study, which prospectively evaluated the effectiveness of IVR for any indications in real-life settings, showed that BCVA change from baseline in DME patients differs between -0.3 to +6.9 letters with mean numbers of IVR injections ranging from 2.2 to 6.0 among countries.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent years, the number of ophthalmological consultations declined to a median of around five per year. Smaller real‐world studies of anti‐VEGF and dexamethasone implant use in DME have also shown declining frequency of ophthalmological care within the first year (Best et al., 2018; Bhandari et al., 2020; Egan et al., 2017; Epstein & Amren, 2018; Farinha et al., 2019; Hodzic‐Hadzibegovic et al., 2018; Hrarat et al., 2016; Maggio et al., 2018; Massin et al., 2019; Mitchell et al., 2020; Stefanickova et al., 2018) and up to 4 years after treatment initiation (Epstein & Amren, 2018; Korobelnik et al., 2022; Maggio et al., 2018; Malcles et al., 2017).…”
Section: Discussionmentioning
confidence: 99%